Plasma Rich in Growth Factors Enhances Wound Healing and Protects from Photo-oxidative Stress in Dermal Fibroblasts and 3D Skin Models - Anitua, Eduardo; Pino, Ander; Jaen, Pedro; Orive, Gorka (Current Pharmaceutical Biotechnology, 2016)
Background: Optimal skin repair has been a desired goal for many researchers. Recently, plasma rich in growth factors (PRGF) has gained importance in dermatology proving it is beneficial effects in wound healing and cutaneous regeneration. Objective: The anti-fibrotic, pro-contractile and photo-protective effect of PRGF on dermal fibroblasts and 3D skin models has been evaluated. Method: The effect against TGFβ1 induced myofibroblast differentiation was tested. Cell contractile activity over collagen gel matrices was analyzed and the effect against UV derived photo-oxidative stress was assessed. The effectiveness of PRGF obtained from young aged and middle aged donors was compared. Furthermore, 3D organotypic skin explants were used as human skin models with the aim of analyzing ex vivo cutaneous preventive and regenerative photo-protection after UV exposure. Results: TGFβ1 induced myofibroblast levels decreased significantly after treatment with PRGF while the contractile activity increased compared to the control group. After UV irradiation, cell survival was promoted while apoptotic and ROS levels were noticeably reduced. Photo-exposed 3D explants showed higher levels of metabolic activity and lower levels of necrosis, cell damage, irritation and ROS formation when treated with PRGF. The histological integrity and connective tissue fibers showed lower signals of photodamage among PRGF injected skin models. No significant differences for the assessed biological outcomes were observed when PRGF obtained from young aged and middle aged donors were compared. Conclusion: These findings suggest that this autologous approach might be useful for antifibrotic wound healing and provide an effective protection against sun derived photo-oxidative stress regardless the age of the patient.
Keywords: photo-oxidative stress